Cyclical effects on job-to-job mobility: an aggregated analysis on microeconomic data - Thomas Cornelißen; Olaf Hübler; Stefan Schneck (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2007)
This paper analyses cyclical effects on job-to-job mobility using German data. The focus lies on the influence of the regional unemployment rate and the regional growth of the GDP. Job-to- job transitions are fragmented into external and internal movements. The innovation is to describe mobility using background information why the moves occur because the available empirical labour market literature is in deficit with analyzing the motive why these transitions occur with respect to the business cycle. External movements can be introduced by quits or forced by layoffs, the end of the contract, or other reasons such as bankruptcy of a firm. Internal transitions are classified as promotions and transfers. Our estimates show that job-to-job mobility is strongly affected by the business cycle. External movements are more likely in times of growing GDP and less probable when the unemployment rate increases. For internal transitions our results suggest that Eastern and Western Germanys workers differ in their mobility properties along the business cycle.
Keywords: E32; J62; J63; 330; job-to-job mobility; internal and external moves; promotions; quits; lay-offs; business cycle; Arbeitsmobilität; Konjunktur; Regionale Arbeitslosigkeit; Regionaler Konjunkturzyklus; Deutschland